The Management of HIV Care Services in Central and Eastern Europe: Data from the Euroguidelines in Central and Eastern Europe Network Group - Skrzat-Klapaczyńska, Agata; Kowalska, Justyna D; Afonina, Larisa; Antonyak, Svitlana; Balayan, Tatevik; Begovac, Josip; Bursa, Dominik; Dragovic, Gordana; Gokengin, Deniz; Harxhi, Arjan; Jilich, David; Kase, Kerstin; et al. (International journal of environmental research and public health, 2022)
INTRODUCTION: The COVID-19 pandemic has been challenging time for medical care, especially in the field of infectious diseases (ID), but it has also provided an opportunity to introduce new solutions in HIV management. Here, we investigated the changes in HIV service provision across Central and Eastern European (CEE) countries before and after the COVID-19 outbreak. METHODS: The Euroguidelines in Central and Eastern Europe Network Group consists of experts in the field of ID from 24 countries within the CEE region. Between 11 September and 29 September 2021, the group produced an on-line survey, consisting of 32 questions on models of care among HIV clinics before and after the SARS-CoV-2 outbreak. RESULTS: Twenty-three HIV centers from 19 countries (79.2% of all countries invited) participated in the survey. In 69.5% of the countries, there were more than four HIV centers, in three countries there were four centers (21%), and in four countries there was only one HIV center in each country. HIV care was based in ID hospitals plus out-patient clinics (52%), was centralized in big cities (52%), and was publicly financed (96%). Integrated services were available in 21 clinics (91%) with access to specialists other than ID, including psychologists in 71.5% of the centers, psychiatrists in 43%, gynecologists in 47.5%, dermatologists in 52.5%, and social workers in 62% of all clinics. Patient-centered care was provided in 17 centers (74%), allowing consultations and tests to be planned for the same day. Telehealth tools were used in 11 centers (47%) before the COVID-19 pandemic outbreak, and in 18 (78%) after (p = 0.36), but were represented mostly by consultations over the telephone or via e-mail. After the COVID-19 outbreak, telehealth was introduced as a new medical tool in nine centers (39%). In five centers (28%), no new services or tools were introduced. CONCLUSIONS: As a consequence of the COVID-19 pandemic, tools such as telehealth have become popularized in CEE countries, challenging the traditional approach to HIV care. These implications need to be further evaluated in order to ascertain the best adaptations, especially for HIV medicine.
Keywords: Europe, Eastern; HIV Infections; pandemie; models of care; COVID-19; Pandemics; telehealth; Humans; SARS-CoV-2; východní Evropa; lidé; HIV; Europe; Evropa; Central and Eastern Europe; HIV infekce